Economic and legal action(s) that should governments take in response to the increased likelihood of annual severe losses from western U.S. Forest fires? - Islam, Mohammad Raijul; Akter, Salma; Hasan, Fakhrul (Journal of Economics and Business Letters, 2022)
This paper is based on the forest fires induced economic and environmental losses faced in the western USA, and the actions and initiatives US government should take to tackle this economic and environmental loss. To conduct this research, we use different data sources, and all our data is related to the western USA. By using the cost-benefit analysis technique, we answer both of our research questions. Our results show that if governments and non-profit organizations use cost-benefit technique to measure the forest fire losses, they can minimise the losses. Our research shows that this technique is very efficient to serve this purpose. Due to the unique data set along with a new model, it is sometimes challenging to execute the model. We also showed as to how government and other non-profit organisations can be benefited if they use cost-benefit technique